Efficacy of antioxidants therapy on progression of periodontal disease - A randomized control trial - Jyoti Wasti; Amit Wasti; Ritunja Singh (Wolters Kluwer Medknow Publications, 2021)
Background and Aim: Increased oxidative stress has emerged as one of the prime factors in the pathogenesis of periodontitis. Hence, antioxidant therapy may become a promising tool in the treatment of periodontal disease. Uric acid is a major salivary antioxidant, levels of which decrease in periodontitis. The aim of the present study was to investigate the effect of antioxidant therapy on the progression of periodontal disease. Material and Methods: This is a randomized controlled clinical trial conducted among 48 systemically healthy participants having generalized gingivitis with probing depth <3 mm, plaque index (PI) <1, and no bone and attachment loss. Participants were randomly assigned equally (n = 24) into two groups (test and control) using the lottery method. Full mouth scaling and root planing were performed in both the groups and oral hygiene instructions were given. Periodontal assessment at baseline 1 h after scaling and root planing was done with clinical parameters by a single examiner. Test group was prescribed; the commercially available anti-oxidant containing natural lycopene with green tea extract. Sample collection was done for both the groups at baseline and at the 45th day. Results: It was observed that significantly high results were obtained during intra-group comparison for both modified plaque index and sulcus bleeding index from baseline to 45 days. After treatment, a very highly significant increase (P ≤ 0.001) in the test group and significant (P ≤ 0.05) increase in the control group were observed in salivary uric acid levels. Conclusion: Oral lycopene and green tea extract supplementation is positively associated with salivary uric acid levels and plays an important role in the management of gingivitis.